Cultural Haunting and the Trace of the Colonial Other in Arthur Conan Doyle's Short Fiction - Martín-González, Juan José (My University, 2017)
In Home Truths: Fictions of the South Asian Diaspora in Britain (2002), Susheila Nasta argues that “the arrival in Britain of several generations of black and Asian 'immigrants' in the period following decolonization and Independence was not simply the residue of the end of Empire, it was the culmination of a long but hidden relationship, a relationship that has persistently been written out of the nation's political, cultural and literary histories” (Nasta 3). In light of this statement, this paper aims at tracing the presence of the Colonial Other in late-Victorian culture via a reading of Arthur Conan Doyle’s “The Black Doctor” (1898) and “The Brown Hand” (1899). These under-read tales provide a constructive counterpoint to widespread and far more popular late-Victorian narrations of reverse colonization such as Bram Stoker’s Dracula (1897) or Richard Marsh’s The Beetle (1897), which exemplify the “brutally abjected, demonized or stereotyped” treatment of race in nineteenth-century English literature (Daileader 75). This paper is informed by literary-historical excavations into black British history such as Antoinette Burton's At the Heart of Empire: Indians and the Colonial Encounter (1998), Rozina Visram's Asians in Britain: 400 Years of History (2002) and Peter Fryer's Staying Power: The History of Black People in Britain (1984). Additionally, I draw upon Kathleen Brogan's concept of 'cultural haunting', in which “the individual's or family's haunting clearly reflects the crisis of a larger social group”, to delve into issues of ethnicity, race and exoticism out of “a poorly documented, partially erased cultural history” (Brogan 2). Ultimately, I argue that, although the tales under analysis must necessarily be framed within Western representation of the Colonial Other and they evince traces of Edward Said’s model of Orientalism, they conversely provide a more benign portrayal of the presence of diasporic collectives on Victorian Britain, more aimed at representing issues of integration, transculturation and diaspora rather than contamination and invasion. Key words: cultural haunting, colonial Other, Conan Doyle References: Burton, Antoinette. At the Heart of Empire: Indians and the Colonial Encounter. Berkeley and London: U of California P, 1998. Brogan, Kathleen. Cultural Haunting. Ghosts and Ethnicity in Recent American Literature. Charlottesville and London: U of Virginia P, 1998. Conan Doyle, Arthur. “The Black Doctor.” 1898. Tales of Terror and Mystery. By Conan Doyle. Ohio: Summit Classic P, 2012. ---. “The Brown Hand.” 1899. The Great Keinplatz Experiment and Other Tales of Twilight and the Unseen. By Conan Doyle. Ohio: Summit Classic P, 2012. Daileader, Celia R. Racism, Misogyny and the Othello Myth: Inter-Racial Couples from Shakespeare to Spike Lee. Cambridge: Cambridge UP, 2005. Fryer, Peter. Staying Power: The History of Black People in Britain. London: Pluto P, 1984. Nasta, Susheila. Home Truths: Fictions of the South Asian Diaspora in Britain. Basingstoke: Palgrave, 2002. Visram, Rozina. Asians in Britain: 400 Years of History. London: Pluto P, 2002.
Keywords: Doyle, Arthur Conan, Sir - Crítica e interpretación; Victorian; Conan Doyle; Colonial Other; Haunting